Comparison of Carbon Reserves in Mangrove Sonneratia Alba and Nypa Fruticans in Pangkalan Jambi Village, Bengkalis District Riau Province - Isnaini, Siti; Amin, Bintal; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2020)
This study was conducted in January – February 2020, which was located in Pangkalan Jambi Village, Bukit Batu District, Bengkalis Regency, Riau Province. The purpose of this study was to determine the potential amount of carbon stored in mangrove vegetation area of mangrove forests. The survey method was applied in this study and carbon stock analysis was carried out in the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, University of Riau. Biomass and carbon stocks in N. fruticans is higher compared to S. alba. Based on the mangrove density, the average total biomass of S. alba and N. fruticans were 0,74 tons/ha and 11,65 tons/ha whilst. Their carbon reserves were 0,35 tons/ha and 5,47 ton/ha, respectively. Potential carbon uptake of N. fruticans and S. alba were 20,07 tons/ha and 1,23 tons/ha, respectively. The potential N. fruticans in the village of Pangkalan Jambi is capable of absorbing 16 times large, compared to S. alba